2022
DOI: 10.1007/s11920-022-01350-3
|View full text |Cite
|
Sign up to set email alerts
|

Adapting and Implementing Apps for Mental Healthcare

Abstract: Purpose of ReviewTo describe examples of adapting apps for use in mental healthcare and to formulate recommendations for successful adaptation in mental healthcare settings. Recent FindingsInternational examples are given to explore implementation procedures to address this multitude of challenges. Summary There are only few published examples of adapting apps for use in mental healthcare. From these examples and from results of studies in implementation science in general clinical settings, it can be conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Patients are offered the use of the “blended ALMAMAR” app during their inpatient stay in addition to routine care. The app (named ALMAMAR, Arabic for “path”) is based on CETA (Common Elements Treatment Approach) [ 19 ], a transdiagnostic therapeutic intervention that has already been evaluated in different settings and groups [e.g. 22 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are offered the use of the “blended ALMAMAR” app during their inpatient stay in addition to routine care. The app (named ALMAMAR, Arabic for “path”) is based on CETA (Common Elements Treatment Approach) [ 19 ], a transdiagnostic therapeutic intervention that has already been evaluated in different settings and groups [e.g. 22 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Guided support by health professionals leading to patient recruitment and stabilizing program adherence as well as professional qualification, training and supervision of practitioners seem to be crucial. The process of adapting and implementing apps for inpatient mental healthcare needs to address clinicians, patients and administrative staff [ 19 ]. To date, many clinical practitioners in inpatient settings still lack practical experience with e-mental health care [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical care through smartphone apps and associated sensors is at the cusp of moving from being a topic of research to being implemented in outpatient care. Some apps already exist, that help patients track their symptoms, review and apply content from psychotherapy and perform cognitive training and also support patients in adhering to their medication [41, 42].…”
Section: Elements Enabling a Radical Change In Psychiatrymentioning
confidence: 99%
“…Health apps can improve the diagnosis and prevention of diseases, provide patients with psychoeducation in the face of a shortage of therapists and monitor progress during therapy [41, 43]. Patients may share very sensitive data via apps, which may also be connected to other sensors such as a smartwatch, so strict data protection and data security rules are needed to reduce the risk of data violations [44].…”
Section: Elements Enabling a Radical Change In Psychiatrymentioning
confidence: 99%
“…Previous reports have demonstrated that SDM has a positive impact on patient satisfaction, adherence to treatment, quality of life, and empowerment, including among patients with serious mental illness [ 35 - 38 ]. Consistent with this view, Zielesak et al [ 39 ] pointed out that there remains a significant gap in understanding clinician needs for information in mental health care decision-making, as well as ways to better integrate apps into routine clinical care and provider workflow. Furthermore, providers’ lack of engagement with, or buy-in for, patient-reported health data have been noted as a critical barrier to its use in health care generally, making it a priority to elicit adaptations that may facilitate uptake from the provider perspective [ 40 ].…”
Section: Introductionmentioning
confidence: 99%